Quantifying the qualities of aesthetics in product design using eye-tracking technology - Khalighy, Shahabeddin; Green, Graham; Scheepers, Christoph; Whittet, Craig (International journal of industrial ergonomics, 2015)
This study provides a methodology to quantify the qualities of visual aesthetics in product design by applying eye-tracking technology. The output data of eye-tracking software, consisting of number, duration, and coordinate of eye fixations, are formulated using the fundamental constituent factors of beauty and attractiveness. This methodology has been developed by conducting three eye-tracking experiments and five experiments applying subjective measures which in total more than 300 participants attended. The results of these experiments contributed to the development of an aesthetic formula. The output of this formula was then compared with the declared preferences of a further 200 subjects. This comparison confirmed that the proposed methodology was capable of quantifying and predicting aesthetic preference by only monitoring eye behaviour. •Aesthetic can be quantified using eye-tracking.•Beauty, appropriateness, and novelty are shown to be the major factors in aesthetic.•Appropriateness has the highest impact in aesthetic judgement of a chair.•Contrast, proportion, and pureness are shown to be the major factors in beauty.